Principles of neurotheology - Newberg, Andrew B., 1966- (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub, 2010)
Neurotheology has garnered substantial attention in the academic and lay communities in recent years. Several books have been written addressing the relationship between the brain and religious experience and numerous scholarly articles have been published on the topic, some in the popular press. The scientific and religious communities have been very interested in obtaining more information regarding neurotheology, how to approach this topic, and how science and religion can be integrated in some manner that preserves both. If neurotheology is to be considered a viable field going forward, it.
Cover; Contents; Preface; 1 The Case for a Principia Neurotheologica (Principles of Neurotheology); 2 Definitions in Neurotheology; 3 The Principles of Interaction Between Neuroscience and Theology; 4 General Principles of Neurotheological Investigations; 5 Towards a Neurotheological Hermeneutic; 6 Principles Relating to the Methods of Neurotheological Research; 7 Physiological and Phenomenological Correlates of Spiritual Practices; 8 Reflections on Major Topics of Neuroscience; 9 Reflections on Major Topics of Theology; 10 Epistemological Issues in Neurotheology; Epilogue: Final Conclusions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Psychology, Religious; Experience (Religion); Neurosciences -- Religious aspects; Brain -- Religious aspects; Religion and science; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books